2016
DOI: 10.1186/s13046-016-0285-3
|View full text |Cite|
|
Sign up to set email alerts
|

Radiation-induced miR-208a increases the proliferation and radioresistance by targeting p21 in human lung cancer cells

Abstract: Background: Lung cancer has long been the most dangerous malignant tumor among males in both well developed and poorly developed countries. Radiotherapy plays a critical role in the curative management of inoperable non-small cell lung cancer (NSCLC) and is also used as a post-surgical treatment in lung cancer patients. Radioresistance is an important factor that limits the efficacy of radiotherapy for NSCLC patients. Increasing evidence suggests that microRNAs (miRNAs) possess diverse cellular regulatory role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
131
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 47 publications
1
131
0
1
Order By: Relevance
“…Apoptosis is an important mechanism for the regulation of sensitivity to radiation [9, 27]. We found that overexpression of miR-19b-3p or knockout of TNFAIP3 decreased apoptosis rates of NPC cell lines after irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptosis is an important mechanism for the regulation of sensitivity to radiation [9, 27]. We found that overexpression of miR-19b-3p or knockout of TNFAIP3 decreased apoptosis rates of NPC cell lines after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Using bioinformatic analyses, we found that both miR-19b-3p and TNFAIP3 have a common apoptotic pathway—the NF-κB signaling pathway. Ionizing radiation is known to cause DNA DSBs and leads to lethal injury [9, 28]. IR-induced DSBs trigger a DNA damage response with NF-κB activation as the antiapoptotic factor in most cell types [2932].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has indicated that miRNAs are important regulatory factors involved in various biological processes, including cell differentiation, growth, metastasis and apoptosis (8,9). Aberrant expression of miRNAs has been identified in numerous cancers, including lung and breast cancer and hepatocellular carcinoma (10)(11)(12)(13)(14)(15). Numerous miRNAs may be regarded as potential and novel biomarkers for the diagnosis, therapy and prognosis of numerous types of cancer (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of programmed cell death, apoptosis and autophagy, are launched in normal cells when cell damage repair, especially, DNA damage, is impossible. Programmed cell death induced in stress exposure is not only associated with the extent of DNA damage, but involves a great number of other signaling mechanisms and depends on their interaction [3,4]. The functioning of signaling and metabolic mechanisms is associated with gene expression regulation at the transcriptional and post-transcriptional levels.…”
mentioning
confidence: 99%